2015
DOI: 10.1016/j.jaut.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Type I and II interferon signatures in Sjogren's syndrome pathogenesis: Contributions in distinct clinical phenotypes and Sjogren's related lymphomagenesis

Abstract: Both type I and II interferons (IFNs) have been implicated in the pathogenesis of Sjogren's syndrome (SS). We aimed to explore the contribution of type I and II IFN signatures in the generation of distinct SS clinical phenotypes including lymphoma development. Peripheral blood (PB) from SS patients (n=31), SS patients complicated by lymphoma (n=13) and healthy controls (HC, n=30) were subjected to real-time PCR for 3 interferon inducible genes (IFIGs) preferentially induced by type I IFN, 2 IFIGs preferentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
185
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 214 publications
(192 citation statements)
references
References 57 publications
6
185
0
1
Order By: Relevance
“…Taking this into account, it became apparent that both type I and type II IFN-stimulated genes can be upregulated in peripheral blood and salivary gland tissue of pSS patients. [16][17][18] Based on a small set of mRNA transcripts that are preferentially induced by either type I IFN or type II IFN, it was concluded that in the peripheral blood of pSS patients type I IFN-stimulated genes appear to dominate, whereas the opposite is the case in the glandular tissue where type II IFN-stimulated genes are the most pronounced. [17,18] Various approaches and definitions are being used to calculate an IFN score and to assign a type I or type II IFN signature to pSS patients.…”
Section: Editorialmentioning
confidence: 99%
See 4 more Smart Citations
“…Taking this into account, it became apparent that both type I and type II IFN-stimulated genes can be upregulated in peripheral blood and salivary gland tissue of pSS patients. [16][17][18] Based on a small set of mRNA transcripts that are preferentially induced by either type I IFN or type II IFN, it was concluded that in the peripheral blood of pSS patients type I IFN-stimulated genes appear to dominate, whereas the opposite is the case in the glandular tissue where type II IFN-stimulated genes are the most pronounced. [17,18] Various approaches and definitions are being used to calculate an IFN score and to assign a type I or type II IFN signature to pSS patients.…”
Section: Editorialmentioning
confidence: 99%
“…[16][17][18] Based on a small set of mRNA transcripts that are preferentially induced by either type I IFN or type II IFN, it was concluded that in the peripheral blood of pSS patients type I IFN-stimulated genes appear to dominate, whereas the opposite is the case in the glandular tissue where type II IFN-stimulated genes are the most pronounced. [17,18] Various approaches and definitions are being used to calculate an IFN score and to assign a type I or type II IFN signature to pSS patients. Despite these discrepancies is it clear that not all pSS patients upregulate type I and II IFN genes to the same extent and three groups of IFN profiles have been identified in pSS patients: type I IFN dominant, type II IFN dominant, or a mixedtype I/II IFN phenotype.…”
Section: Editorialmentioning
confidence: 99%
See 3 more Smart Citations